2017
DOI: 10.1177/1010428317701631
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 maintains osteosarcoma invasion after CXCR4 suppression in bone marrow microenvironment

Abstract: The major cause of death in osteosarcoma is the invasion and metastasis. Better understanding of the molecular mechanism of osteosarcoma invasion is essential in developing effective tumor-suppressive therapies. Interaction between chemokine receptors plays a crucial role in regulating osteosarcoma invasion. Here, we investigated the relationship between CXCR7 and CXCR4 in osteosarcoma invasion induced by bone marrow microenvironment. Human bone marrow mesenchymal stem cells were co-cultured with osteosarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…They mentioned that CXCR7 was involved in modulating tumor microenvironment, tumor cell migration and apoptosis, thus revealing that these complex interactions provided insight into targeting CXCR7 as a potential anticancer therapy. Similar to our experimental observation in Figure 5, in (Han, 2017), suppressing CXCR4 was not enough to obstruct osteosarcoma invasion in bone marrow microenvironment, as CXCR7 was activated to sustain invasion. Therefore, they suggested that inhibiting both CXCR4 and CXCR7 could be a promising strategy in controlling osteosarcoma invasion, which perfectly matches our prediction and observation in LNCaP prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
“…They mentioned that CXCR7 was involved in modulating tumor microenvironment, tumor cell migration and apoptosis, thus revealing that these complex interactions provided insight into targeting CXCR7 as a potential anticancer therapy. Similar to our experimental observation in Figure 5, in (Han, 2017), suppressing CXCR4 was not enough to obstruct osteosarcoma invasion in bone marrow microenvironment, as CXCR7 was activated to sustain invasion. Therefore, they suggested that inhibiting both CXCR4 and CXCR7 could be a promising strategy in controlling osteosarcoma invasion, which perfectly matches our prediction and observation in LNCaP prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
“…There are always some cross-talks between different pathways in tumor occurrence and development, which provides a comprehensive understanding of tumor occurrence and development. Furthermore, the IL-8/CXCR1 axis and CXCL12/CXCR4/CXCR7 axis are commonly activated in the bone microenvironment when OS metastasis occur [ 29 , 31 , 33 , 39 , 53 ]. IL-8 and CXCL12, as the secreted molecules, are detected easily through peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological analysis shows that CXCR4, receptor of CXCL12, and MMP-9 are overexpressed in OS with lung metastasis patients compared to the patients without metastasis [ 52 ]. CXCL12/CXCR4/CXCR7 was activated when a co-culture of bone marrow mesenchymal stem cells and OS cells ( Table 1 ) [ 53 ]. At the same time, the activation of CXCL12/CXCR4/CXCR7 in the co-culture model boosts the OS invasion [ 53 ].…”
Section: Bone Microenvironment and Os Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Human Mesenchymal Stem Cells (hMSCs) play also a major role in the communication between tumor cells and their microenvironment, as highlighted by recent studies, including increased proliferation and migration of tumor cells. On one hand, bone marrow MSCs promote migration and invasion through direct secretion of several cytokines such as C-X-C motif chemokine ligand 12 (CXCL12) that binds to C-X-C motif chemokine receptor 4 (CXCR4) or CXCR7 on osteosarcoma associated with lower overall patient survival [26,27,28]. Interleukin-6, secreted by MSCs, contributes to promote metastatic dissemination of osteosarcoma [29,30].…”
Section: Tumor Microenvironment: Crucial Role In Bone Sarcoma Tumomentioning
confidence: 99%